TikTok, the new social platform for luxury brands - Rodríguez Hernández, Marina; Vázquez Sacristán, Isabel A. (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Given the relevance acquired by the social network TikTok among new generations, we have selected the luxury companies present in the Best Global Brands 2023 report; we have verified their official presence on TikTok; we carried out a comparative study of the profiles in relation to a series of key variables such as the number of followers, the publications made, the likes obtained; and, finally, we did an analysis of the most shared contents to detect the characteristics of those that obtain the best results and their possible influences on current visual culture.